2005
DOI: 10.1542/peds.2004-1854
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Recurrent Abdominal Pain From 2 to 6 Years of Age: Results of a Large, Population-Based Study

Abstract: In a large, population-based, cohort study, RAP was found to be increasingly common up to the age of 6 years. Children with RAP at a young age have a high risk of RAP later in childhood. RAP is associated with other somatic pain symptoms among children and with symptoms of anxiety among children and their mothers. These findings highlight the high prevalence and continuity of RAP through early childhood and the importance of considering psychological symptoms for these children and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
78
3
11

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 25 publications
6
78
3
11
Order By: Relevance
“…Although not studied yet, explanations for this age peak might be school attendance and its associated anxieties. The observed age peak of 12 to 16 years for girls in our study might be explained by menarche or dysmenorrhea.In the medical literature a variety of expressions are used for childhood nonorganic abdominal pain: recurrent abdominal pain; 1,3,20,22 chronic abdominal pain; 23,24 functional abdominal pain; 25 and nonspecifi c abdominal pain.26,27 Most of these terms include a minimal duration of abdominal pain, usually 3 months. This time criterion was arbitrarily set by Apley et al, who were the fi rst to describe the pain syndrome in 1958.…”
mentioning
confidence: 99%
“…Although not studied yet, explanations for this age peak might be school attendance and its associated anxieties. The observed age peak of 12 to 16 years for girls in our study might be explained by menarche or dysmenorrhea.In the medical literature a variety of expressions are used for childhood nonorganic abdominal pain: recurrent abdominal pain; 1,3,20,22 chronic abdominal pain; 23,24 functional abdominal pain; 25 and nonspecifi c abdominal pain.26,27 Most of these terms include a minimal duration of abdominal pain, usually 3 months. This time criterion was arbitrarily set by Apley et al, who were the fi rst to describe the pain syndrome in 1958.…”
mentioning
confidence: 99%
“…In a large population-based study, the prevalence of abdominal pains in preschool-age children was found to be high (39.7%) [1]. However in this sample the presence of recurrent abdominal pains (RAP), according to Apley's criteria, was much lower (3.8%-11.8%).…”
mentioning
confidence: 68%
“…Moreover, children with RAP are more likely to experience headache than those without RAP, 27.7% vs. 14.3% at 42 months and 55.4% vs. 37.8% at 81 months, with a statistically significant difference [1].…”
mentioning
confidence: 93%
“…Tilbagevendende funktionelle somatiske symptomer oce i form af mavesmerter, hovedpine, traethed eller smerter i arme eller ben (voksevaerk) udgør betydelige kliniske problemer, idet denne type klager forekommer hos ca. 10-15% af alle børn og hyppigt medfører kontakt til sundhedsvaesenet (Offord 1987, Goodman 1991, Ramchandani 2005. Kontakten sker som regel til egen laege eller paediater grundet symptomernes fysiske karakter.…”
Section: En Udviklingsorienteret Biopsykosocial Tilgang I Klinikkenunclassified